Strangulated diaphragmatic hernia presenting at 7 weeks of life as intractable shock. (3rd October 2013) - Ismail, Abdul Qader Tahir; Alake, Oluwaseyi; El-Shimy, Nagui
Abstract : A 7-week-old infant presented to hospital pale and floppy, with 5 s capillary refill time. Blood gas showed severe acidosis (pH 6.86, partial pressure of carbondioxide 10.55 kPa, base excess 21.1). Hypotension persisted despite several fluid boluses so she was intubated and started on inotropic support. A chest X-ray revealed a congenital diaphragmatic hernia (CDH). Despite steroids and blood transfusions she remained unstable, and could not be resuscitated following cardiac arrest. Postmortem revealed 39 cm of herniated, necrotic colon. 5–25% of CDH presents after the neonatal period, and while not associated with pulmonary hypoplasia is primarily still a diaphragmatic defect. In late presenting cases, herniation occurs shortly prior to developing symptoms; therefore, an antenatal ultrasound (US) cannot pick it up. If we could diagnose the isolated diaphragmatic defect antenatally, this would allow elective postnatal surgical closure. This is not feasible currently; however, with the advent of antenatal three-dimensional US scans it may be possible in the future.